Synthesis and functionalization of dendritic polyglycerol-based nanogels: application in T cell activation. Issue 1 (9th December 2021) - Reisbeck, Felix; Wedepohl, Stefanie; Dimde, Mathias; Schmitt, Ann-Cathrin; Dernedde, Jens; Álvaro-Benito, Miguel; Freund, Christian; Haag, Rainer
Abstract : Synthesis of a dPG- and NG-based nanoplatform conjugated to avidin for the multivalent display of biotinylated biomolecules. Carriers were coupled to antibodies and their capability to activate T cells was assessed, showing a multivalency effect. Abstract : The concept of multivalency finds various applications in the fields of chemistry and biology, relying on the principle that multiple weak interactions can lead to strong adhesive forces. Polymeric carriers are promising tools to translate these properties into the field of biomedicine, especially upon functionalization by active biomolecules, such as antibodies. In this study we report on the synthesis of dendritic polyglycerol (dPG) and dPG-based nanogels (NGs) as platforms for the multivalent display of molecules and their potential application as carrier units. Macromolecules based on dPG were synthesized and NGs were generated by strain-promoted azide–alkyne cycloaddition (SPAAC) by inverse nanoprecipitation under mild conditions. Scale-up screening rendered a reproducible method for a batch size of up to 50 mg for the formation of NGs in a size range of 150 nm with narrow dispersity. Dye-labelled bovine serum albumin (FITC-BSA) was chosen as a model protein and showed successful conjugation to the carriers, while the protein's secondary structure was not affected. Consequently, cyanine-5-amine (Cy5-NH2 ) and avidin (Av) were conjugated in order to exploit the strong avidin-biotin interaction, facilitating the directed attachment of a myriad of biotinylated (bio)molecules. As a proof-of-concept, the biotinylated monoclonal antibodies (mAbs) α-CD3 and α-CD28 were attached to the platforms and their capability to activate T cells was assessed. Experiments were performed with a Jurkat reporter cell line which expresses green fluorescent protein (GFP) upon activation, providing a rapid and reliable readout by flow cytometry. Carriers clearly outperformed conventional compounds for activation ( i.e. antibodies crosslinked with anti-IgG antibody) at significantly lower dosages. These findings could be confirmed by confocal laser scanning microscopy (CLSM), showing accumulation of the functional nanoplatforms at the cell surface and cytoplasmic GFP expression (>95% activation of cells for the multivalent conjugates at 10 μg mL −1 compared to 37% activation with conventionally crosslinked mAbs at 25 μg mL −1 ), whereas carriers without mAbs could not activate cells. As the attachment of biotinylated molecules to the functional nanoplatforms is straightforward, the results obtained show the great potential of our platforms for a broad range of applications.